News on foreign war versus local ‘war’: Perception of Malaysian audience - Ibrahim, Faridah; Sayed Halem Shah, Dil Froz Jan; Yunus Shah, Norzita; Chang, Peng Kee; Mustaffa, Normah (Elsevier Ltd., 2014)
For the past decades, we have witnessed many wars through the mass media, both traditional and new media.We tend to view foreign wars with mixed feelings but what happens if the war is happening locally? The purpose of this research is to see what is the perception of Malaysians with regard to ‘war’ that happened locally.This research surveyed Malaysians respondents in the Klang Valley to study their perceptions regarding the Lahad Datu incident in Sabah.Findings from this research showed that Malaysians were saddened by foreign wars and sympathize with those experiencing ‘war’ or conflict.